Hakekat Hukuman Dalam Pendidikan Islam - Jajang Aisyul Muzakki (Universitas Muhammadiyah Sidoarjo, 2017)
Punishment is something that is prescribed and one of the most successful educational tools that educators may require from time to time. But there is a very excessive use of this mean, making it as if the dangerous tool and resulted in the opposite. A teacher is required to provide the best for his students, including punishment. Do not let when giving the punishment, stuents looked at it as a torture. The educational tool in the form of punishment is something unpleasant in return for a bad deed. But keep in mind that in the punishment, a teacher must have the motivation for giving punishment that can be a good motive for the learners. Indeed, the purpose of imposing punishment in Islamic Education is nothing but to provide guidance and improvement. Therefore, it should be noted the character and condition of the child must be concerned before a teacher sentenced him. By understanding the meaning of punishment in Islamic Education based on al-Qur'an and hadith, it is expected that punishment could generate positive meaning to the learners.